MN PLAN STATUS REPORT - BROZEK, MICHAEL; NELSON, DANIEL (Tufts Archival Research Center, 2007)
Letter from Michael F. Brozek and Daniel C. Nelson, to William A. Cannell regarding the legislative plan in Minnesota to combat anti-tobacco activities.